Looking like what you are sexual style, race, and lesbian identity - Walker, Lisa (The cutting edge: Lesbian life and literature, 2001)
Looks can be deceiving, and in a society where one's status and access to opportunity are largely attendant on physical appearance, the issue of how difference is constructed and interpreted, embraced or effaced, is of tremendous import. Lisa Walker examines this issue with a focus on the questions of what it means to look like a lesbian, and what it means to be a lesbian but not to look like one. She analyzes the historical production of the lesbian body as marked, and studies how lesbians have used the frequent analogy between racial difference and sexual orientation to craft, emphasize, or deny physical difference. In particular, she explores the implications of a predominantly visible model of sexual identity for the feminine lesbian, who is both marked and unmarked, desired and disavowed. Walker's textual analysis cuts across a variety of genres, including modernist fiction such as The Well of Loneliness and Wide Sargasso Sea, pulp fiction of the Harlem Renaissance, the 1950s and the 1960s, post-modern literature as Michelle Cliff's Abeng, and queer theory.
Keywords: arts; corps; discipline; identités LGBTQIA2+; littérature; personnes lesbiennes; thématiques; études littéraires